Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Donkeys as livestock guardians against predators in an African savanna - Dhananjaysinh Y. Jhala; Dallas Ruble; Utarera Katjavivi; Stijn Verschueren; Robin M. Cook; Laurie L. Marker; Bogdan Cristescu (European Journal of Wildlife Research, 2026)

A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

Stakeholder values on the management of African elephants for large tree conservation in protected areas - Robin M. Cook; Ed T. F. Witkowski; Michelle D. Henley (European Journal of Wildlife Research, 2025)
Stakeholder perspectives play a crucial role in conservation decisions, particularly for species with complex ecological and social impacts, such as African savanna elephants ( Loxodonta africana ). In a South African protected area experiencing high elephant densities and significant tree loss, we surveyed 170 stakeholders, including conservation managers, property owners, tourists, and tourism personnel. Using a Likert scale and thematic analysis, we evaluated their attitudes towards tree protection, waterhole closures, contraception, and culling to mitigate elephant impacts on large trees. Results showed strong support for waterhole closures and tree protection, particularly among younger conservation managers and property owners, who viewed these methods as effective in dispersing elephant populations and safeguarding valuable trees. Conversely, tourists and younger stakeholders preferred non-lethal strategies like contraception, while conservation managers expressed practical concerns about its feasibility. Culling emerged as the most divisive strategy, supported primarily by older and male stakeholders in conservation but largely opposed by tourists due to ethical concerns. The chord diagram illustrated distinct patterns, with conservation managers aligning more with waterhole closures and culling, while property owners and tourists favoured tree protection and contraception. These findings highlight the diversity in stakeholder values, shaped by demographic factors, and underscore the need for adaptive, context-specific management strategies. Our study provides a framework for conservation policies that balance ecological objectives with social acceptability, promoting sustainable coexistence between elephants, large trees, and diverse stakeholder interests.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

The value of seabird foraging ranges as a tool to investigate potential interactions with offshore wind farms - Ian D. Woodward; Chris B. Thaxter; Ellie Owen; Mark Bolton; Robin M. Ward; Aonghais S.C.P. Cook (Ocean & Coastal Management, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Survival trends (2008–2020) of three tree species in response to elephant impact, environmental variation, and stem wire-netting protection in an African savanna - Robin M. Cook; Ed T.F. Witkowski; Michelle D. Henley (Forest Ecology and Management, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Melissopalynological investigations of seasonal honey samples from the Greater Kruger National Park, Savanna biome of South Africa - Nikiwe Ndlovu; Frank H. Neumann; Michelle D. Henley; Robin M. Cook; Chevonne Reynolds (Palynology, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Inclusion of discards in stock assessment models - Robin M. Cook (Fish and Fisheries, 2019)
A large portion of the catch in many stocks may comprise discards which need to be accounted for in assessments in order to avoid bias in estimates of fishing mortality, stock biomass and reference points. In age‐structured assessment models, discards are sometimes treated as a separate fleet or are added to the landings before fitting so that information about discard behaviour and sampling error is lost. In this paper, an assessment model is developed to describe the discard process with size as a covariate while retaining age‐structured population dynamics. Discard size selection, high grading and bulk dumping of fish at sea are modelled so that the temporal dynamics of the process can be quantified within the assessment. The model is used to show that discarding practices have changed over time in a range of Northeast Atlantic demersal fish. In some stocks, there is a substantial increase in high grading and evidence for bulk discarding which can be related to regulatory measures. The model offers a means of identifying transient effects in the discard process that should be removed from both short‐term forecasts and equilibrium reference point calculations.

Population trends of bycatch species reflect improving status of target species - Robin M Cook; Michael R Heath (Fish and Fisheries, 2018)
Synthesis studies of fish stocks worldwide suggest improving status of mainly target species that are fully assessed. Other analyses, primarily based on catch data alone, but which include a wider range of species as well as bycatch, present a different view. Catch‐only analyses could be more robust if fishery‐independent data were used and discards accounted for. We develop a model that uses only survey biomass at length and landings data to estimate fishing mortality, spawning stock biomass ( SSB ) and discards. An analysis of species from the North Sea shows the model results compare well with most fully assessed stocks. When applied to bycatch species with limited data, trends in fishing mortality and SSB typically reflect those of the target species. In the last decade, mean fishing mortality rates have tended to decline, while mean SSB has increased. Despite increasing SSB , recent mean recruitment appears to have been lower than previously which may limit future biomass recovery. Species usually associated with more northerly distributions appear to show the greatest effect of weaker recruitment, which may be linked to climate. Estimated discards have tended to decline in magnitude as a result of reduced fishing mortality and associated lower total catches. The model offers a simple way to use both landings and survey data to obtain more detailed population trends for data limited species.

The effects of foundation species on community assembly: a global study on alpine cushion plant communities - Zaal Kikvidze; Robin W. Brooker; Bradley J. Butterfield; Ragan M. Callaway; Lohengrin A. Cavieres; Bradley J. Cook; Christopher J. Lortie; Richard Michalet; Francisco I. Pugnaire; Sa Xiao; Fabien Anthelme; Robert G. Björk; et al. (Ecology, 2015)
Foundation species can change plant community structure by modulating important ecological processes such as community assembly, yet this topic is poorly understood. In alpine systems, cushion plants commonly act as foundation species by ameliorating local conditions. Here, we analyze diversity patterns of species' assembly within cushions and in adjacent surrounding open substrates (83 sites across five continents) calculating floristic dissimilarity between replicate plots, and using linear models to analyze relationships between microhabitats and species diversity. Floristic dissimilarity did not change across biogeographic regions, but was consistently lower in the cushions than in the open microhabitat. Cushion plants appear to enable recruitment of many relatively stress‐intolerant species that otherwise would not establish in these communities, yet the niche space constructed by cushion plants supports a more homogeneous composition of species than the niche space beyond the cushion's influence. As a result, cushion plants support higher α‐diversity and a larger species pool, but harbor assemblies with lower β‐diversity than open microhabitats. We conclude that habitats with and without dominant foundation species can strongly differ in the processes that drive species recruitment, and thus the relationship between local and regional species diversity.